Fostering Youth's Queer Activism in Secondary Classrooms: Youth Choice and Queer‐Inclusive Curriculum. Issue 6 (4th April 2021) - Schey, Ryan
Abstract: Previous research has revealed that U.S. schools are hostile and unsafe for queer youth, yet school‐based supports, such as LGBTQ‐inclusive curriculum, are associated with more welcoming schools. Studies focusing on inclusive curriculum have implicitly characterized this curriculum didactically, in other words, as a direct intervention into the homophobia, transphobia, and ignorance of straight, cisgender students. Drawing on a yearlong literacy ethnography at a public high school in a Midwestern U.S. city, I explored the complex layers of queer‐inclusive curriculum's significance. Focusing on two illustrative Socratic seminar assignments from a sophomore humanities course, I argue that the queer‐inclusive curriculum was consequential less because it functioned didactically and more because it fostered a classroom context where youth's already existing queer activism could flourish. These classroom examples suggest the importance of literacy educators collaborating with youth to offer choice alongside curriculum that represents religiously and racially diverse queer communities, queer joy, and possibilities beyond binaries.